“We Combat Veterans Have a Responsibility to Ourselves and Our Families:” Domesticity and the Politics of PTSD in Memoirs of the Iraq and Afghanistan Wars - Kieran, David (American Studies, 2018)
Amid an epidemic of post-traumatic stress disorder among veterans returning from Iraq and Afghanistan, advocates for improved mental health care have persistently replicated a post-Vietnam emphasis on the threat that PTSD poses to the nuclear family as they have critiqued an understaffed, unresponsive veterans' mental health care system. Three of the most significant memoirs that deal with veterans' mental health, however, have not embraced this discourse and have instead inverted it, positing that military mental health care is either sufficient or unnecessary that that veterans who recommit to normative domesticity while maintaining their military identities will find readjustment relatively unproblematic. In doing so, these memoirs undermine a discourse that calls for improved veterans mental healthcare.